Magnetic Resonance Imaging of the Lumbar Spine in Young Arabs with Low Back Pain - Al-saeed, Osama (Korean Society of Spine Surgery, 2012)
STUDY DESIGN: A prospective study. PURPOSE: To Investigate the prevalence of magnetic resonance imaging (MRI) changes of the lumbar spine in low back pain (LBP) and the associated risk factors in young Arab population. OVERVIEW OF LITERATURE: Studies on the prevalence of MRI findings and their relationship with LBP have been conducted; these have occurred in adult populations in developed countries. The prevalence of MRI changes in the young Arab population with LBP is not known. METHODS: Two hundred and fourteen patients of Arab origin in the 16 to 29 year age group with LBP symptoms underwent MRI examinations. The prevalence of MRI changes in the lumbar spine and associated risk factors were determined and compared to age, race, and gender-matched controls. RESULTS: A majority (64%) of the patients with LBP (138 out of 214) were found to have MRI evidence of degenerative disc disease (DD) compared to 10% (22 out of 214) in the control group. The majority (61%) of patients had multiple level disease, most commonly involving the lowest 2 disc levels. Reduced signal of the disc followed by disc bulge was the most common MRI features seen in the symptomatic subjects. Obesity correlated with MRI prevalence of abnormalities, while activity demonstrated a positive trend. CONCLUSIONS: The MRI prevalence of DD among the young Arab patients with LBP is high when compared to other reports in literature. Obesity correlated with MRI prevalence of abnormalities while activity demonstrated a positive trend.